2021
DOI: 10.1017/s0021932021000237
|View full text |Cite
|
Sign up to set email alerts
|

What has comprehensive HIV/AIDS knowledge got to do with HIV testing among men in Kenya and Mozambique? Evidence from Demographic and Health Surveys

Abstract: People living with undiagnosed HIV are big contributors to the transmission of the virus. Although measures have been made to scale up HIV prevention and voluntary counselling and testing in sub-Saharan Africa, testing coverage remains low in many sub-Saharan African countries, including Mozambique and Kenya, where most people live with HIV/AIDS. Studies have shown that, in most countries in sub-Saharan Africa, men are less likely to test for HIV compared with women. This study examined the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
2
6
1
Order By: Relevance
“…Our findings are consistent with those from Ethiopia, 7 Zimbabwe, 5 Kenya and Mozambique. 9 Evidence of a positive association between comprehensive knowledge of HIV and HIV testing uptake stresses the importance of continued and effective dissemination of health messages about HIV/AIDS, HIV testing services and the benefits of getting tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with those from Ethiopia, 7 Zimbabwe, 5 Kenya and Mozambique. 9 Evidence of a positive association between comprehensive knowledge of HIV and HIV testing uptake stresses the importance of continued and effective dissemination of health messages about HIV/AIDS, HIV testing services and the benefits of getting tested.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found that certain socioeconomic and demographic characteristicsage, 5,6 marital status, [6][7][8] educational levels, [6][7][8] occupation, 7 wealth [5][6][7][8] and place of residence 5,8 are significantly associated with HIV testing uptake. Moreover, research has demonstrated that comprehensive knowledge of HIV is associated with higher HIV testing uptake, 5,7,9 while stigma and discrimination of HIV are associated with lower HIV testing uptake. 5 Additionally, Thapa et al 10 found that women with positive attitudes about safer sex negotiation had higher odds of being tested for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the DHS is a reliable source of data, and numerous African studies have validated this survey to measure comprehensive knowledge about HIV and AIDS [8,15,16,24,27,28]. Further details on the method of data collection and the questionnaires used can be found in the DHS Angola 2015 report [29].…”
Section: Methodsmentioning
confidence: 99%
“…The concept of comprehensive knowledge of HIV and AIDS includes an understanding of the transmission of HIV and the ability to refute misconceptions about HIV and AIDS [10]. Although this concept can vary between studies and regions [10,[15][16][17], it is widely accepted that having a comprehensive knowledge of HIV can be the first step toward HIV-testing, modifying unsafe behaviors among populations at risk, and the acceptance of treatment [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation